Positive psychology and the search for happiness at work - Porras Velasquez, Nestor Raul (Utan Kayu Publishing, 2024)
This study aims to develop an analysis model and psychosocial and cultural interventions that specifically adapt and extend Martin Seligman's proposed framework of happiness in the workplace. Focusing on the work context in Colombia, this research poses the question: